2000
DOI: 10.1007/bfb0084242
|View full text |Cite
|
Sign up to set email alerts
|

Coherent phonons in condensed media

Abstract: Abstract. The impulsive excitation and phase-sensitive detection of coherent phonons and phonon-polaritons provide a detailed insight i n to the dynamical properties of matter. The experiments are based on optical pump-probe techniques with femtosecond time resolution. These techniques enable the detection of amplitude and phase of the coherent lattice motion simultaneously. F requencies in the THz range and dephasing times in the picosecond range can be obtained with high accuracy. Especially in semiconductor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
132
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 123 publications
3
132
1
Order By: Relevance
“…The vanishing anisotropy for n-GaAs indicates that the generation of both coherent LO and LOPC modes is dominated by TDFS, in agreement with early studies that reported on the L− mode of n-doped GaAs 6-8 . Our results confirm that ultrafast carrier separation by the built-in field in the depletion layer launches not only coherent LO phonons within the depletion layer of n-GaAs, but also coherent LOPC modes in the adjacent bulk via ultrafast drift-diffusion current 1,7 . The dominance of the TDFS generation mechanism can explain the distinct power dependence of the LO amplitude in n-GaAs [ Fig.…”
Section: A Generation Mechanism Of Lo and Lopc Modessupporting
confidence: 71%
See 2 more Smart Citations
“…The vanishing anisotropy for n-GaAs indicates that the generation of both coherent LO and LOPC modes is dominated by TDFS, in agreement with early studies that reported on the L− mode of n-doped GaAs 6-8 . Our results confirm that ultrafast carrier separation by the built-in field in the depletion layer launches not only coherent LO phonons within the depletion layer of n-GaAs, but also coherent LOPC modes in the adjacent bulk via ultrafast drift-diffusion current 1,7 . The dominance of the TDFS generation mechanism can explain the distinct power dependence of the LO amplitude in n-GaAs [ Fig.…”
Section: A Generation Mechanism Of Lo and Lopc Modessupporting
confidence: 71%
“…In transient reflectivity measurements, a nuclear displacement Q associated with the LO phonon oscillation induces a change in reflectivity R through the refractive index n and the susceptibility χ. In a first-order approximation the change ∆R is given by 1,14 :…”
Section: Theoretical Background a Generation And Detection Of Comentioning
confidence: 99%
See 1 more Smart Citation
“…Here, at high electric fields, field induced tunneling into above-barrier continuum states leads to a rapid dephasing of Bloch oscillations. The associated polarization change provides an additional excitation process for coherent LO phonons.1 Introduction Time-resolved investigations of resonantly coupled excitations involving phonons, such as coupled plasmon-phonon modes or phonon-polaritons, are one of the most intriguing subjects of coherent phonon spectroscopy (for a review see, e.g., [1]). …”
mentioning
confidence: 99%
“…1 Introduction Time-resolved investigations of resonantly coupled excitations involving phonons, such as coupled plasmon-phonon modes or phonon-polaritons, are one of the most intriguing subjects of coherent phonon spectroscopy (for a review see, e.g., [1]). …”
mentioning
confidence: 99%